Critical Powder Loading and the Rheology of Nanosized Cemented Carbide with Titanium Carbide as Grain Growth Inhibitor for Injection Molding - M Amin, Sri Yulis; Othman, Mohd Hilmi; Ibrahim, Mohd Halim Irwan; Shahbudin, Siti Nurshahmira (International Journal of Integrated Engineering, 2018)
The purpose of this paper is to determine the critical powder loading of WC-Co and to study the effect of TiC powder on the rheological behavior of MIM feedstock. WC-TiC-6Co metal powder was taken as raw material. 60% (mass fraction) palm stearin and 40% low density polyethylene were employed as binders to prepare injection feedstock. Three feedstocks were prepared at different TiC % loadings of 0.5, 0.75, and 1.0 (by weight). A homogeneous metal powders is formed by using ball mill mixer and mixed together with binder system by using Brabender mixer. Based on the result obtained, it was concluded that feedstock with 0.75 wt.% TiC powder show a good pseudo-plastic behavior within acceptable ranges in MIM